A figura do Comitê de Auditoria no mercado de capitais brasileiro - Mazon, Jonathan Singh (2022)
The primary objective of this dissertation is to provide Brazilian listed companies with a roadmap for the successful implementation and effective functioning of Audit Committees (COAUD) within those companies’ governance structures. An additional objective is to provide subsidies to potential members of this governance body and to professionals from other areas who want to broaden their perspectives regarding the challenges faced, the desirable profile traits for these professionals and the duties usually delegated to COAUD, among other aspects. Bearing in mind the relatively new nature of this body in the Brazilian business environment and the variety of factors that may negatively impact its effectiveness, we sought to map the main weaknesses and risks related to the practice observed in Brazilian publicly traded companies. Based on this survey, the author sought to translate into specific recommendations and points for reflection the combination of Brazilian and international best practices and the first-hand knowledge accumulated by experienced governance professionals in Brazil. In this way, the present study seeks to complement, whenever relevant, the laws and regulations that generically regulate the COAUD in Brazil.